2023
DOI: 10.1039/d3ta05763a
|View full text |Cite
|
Sign up to set email alerts
|

Solar-driven photocatalytic removal of NO over a concrete paving eco-block containing black TiO2

Pengyu Dong,
Cunxia Wang,
Junjian Tan
et al.

Abstract: The dispersion containing black TiO2 photocatalyst was prepared and sprayed onto the concrete's surface to achieve a black TiO2-based photocatalytic concrete paving Eco-block, and its photocatalytic NO removal ratio is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Figure a showed that the Bi 4f spectrum could be decomposed into two peaks at 159.16 and 164.47 eV, belonging to Bi 4f 7/2 and Bi 4f 5/2 , respectively, indicating the presence of Bi 3+ Figure b showed the O 1s XPS spectrum, with peaks at 529.89, 530.45, and 531.60 eV corresponding to lattice oxygen, , carbonate species, and surface hydroxyl groups in BiO­[ClBrI­(CO 3 ) 0.5 ], respectively . The C 1s peak in BiO­[ClBrI­(CO 3 ) 0.5 ] had three characteristic peaks, with the peak at 288.59 eV attributed to CO 3 , and the peaks at 286.32 and 284.72 eV belonged to C–O and C–C, respectively (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a showed that the Bi 4f spectrum could be decomposed into two peaks at 159.16 and 164.47 eV, belonging to Bi 4f 7/2 and Bi 4f 5/2 , respectively, indicating the presence of Bi 3+ Figure b showed the O 1s XPS spectrum, with peaks at 529.89, 530.45, and 531.60 eV corresponding to lattice oxygen, , carbonate species, and surface hydroxyl groups in BiO­[ClBrI­(CO 3 ) 0.5 ], respectively . The C 1s peak in BiO­[ClBrI­(CO 3 ) 0.5 ] had three characteristic peaks, with the peak at 288.59 eV attributed to CO 3 , and the peaks at 286.32 and 284.72 eV belonged to C–O and C–C, respectively (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Figure b showed the O 1s XPS spectrum, with peaks at 529.89, 530.45, and 531.60 eV corresponding to lattice oxygen, , carbonate species, and surface hydroxyl groups in BiO­[ClBrI­(CO 3 ) 0.5 ], respectively . The C 1s peak in BiO­[ClBrI­(CO 3 ) 0.5 ] had three characteristic peaks, with the peak at 288.59 eV attributed to CO 3 , and the peaks at 286.32 and 284.72 eV belonged to C–O and C–C, respectively (Figure c). Figure d showed the high-resolution spectrum of Cl 2p, with binding energy peaks located at 197.92 and 199.50 eV attributed to Cl 2p 3/2 and Cl 2p 1/2 , respectively, confirming the presence of Cl – in BiO­[ClBrI­(CO 3 ) 0.5 ]. , The binding energies of Br 3d at 68.19 and 69.26 eV correspond to Br 3d 5/2 and Br 3d 7/2 , respectively (Figure e) .…”
Section: Resultsmentioning
confidence: 99%
“…Although significant progress has been made in improving the removal efficiency of photocatalytic NO, the widespread industrial application still faces several challenges. 6–8 Firstly, most current photocatalysts have limited-service life and are prone to poisoning. For example, Duan et al developed amorphous carbon nitride with (N3C) nitrogen void by a one-step calcination method which broadened the photocatalytic response range and reduced reaction barriers by an order of magnitude, converting NO into NO 3 − for deep removal of NO.…”
Section: Introductionmentioning
confidence: 99%